Moldova : Rekindling Economic Dynamism - World Bank Group (World Bank, Washington, DC, 2019)
This current Country Economic Memorandum is intended to provide a comprehensive analysis of growthconstraints and recommendations. While it updates some aspects of these earlier studies, its main focus is on enterprise performance. Insofar as enterprise performance occurs in a larger institutional context, this focus necessarily touches on several of the earlier themes, particularly the rule of law, business regulation, and education. The first chapter presents a diagnostic that highlights the problem of falling productivity in the enterprise sector and points to elements of market structure (particularly state ownership) that undermine productivity growth and curtail the growth of the private sector. This chapter also focuses on demand-side issues in export markets, and highlights policy lessons from sectors with high productivity that could drive future growth. A second chapter focuses on foreign firms, which are high productivity enterprises within Moldova, and looks at investment promotion and ways to improve the contribution of Foreign Direct Investment (FDI) to the economy. Subsequent chapters extend the analysis to incentives shaping enterprise performance and opportunities for growth led by the private sector, particularly: competition and regulatory policies (Chapter 3); tax policy insofar as it affects incentives and tax buoyancy that underpin macroeconomic stability (Chapter 4); and finally, education as a crucial input into enterprise development (Chapter 5).